The effect of pressure changes during simulated diving on the pull out strength of glass fiber posts - Meenal Nitin Gulve; Nitin Dilip Gulve (Wolters Kluwer Medknow Publications, 2013)
Background: Scuba diving is one of the fastest growing sports in the world. The objective of this study was to evaluate the effect of pressure variations to which divers are exposed on the pull out strength of glass fiber post luted with different cements. Materials and Methods: In this in vitro study, 120 extracted, single-rooted lower premolars were endodontically treated. They were randomly divided into six groups and restored using the glass fiber post (Ivoclar Vivadent AG) and the following luting agents: Zinc phosphate, conventional glass ionomer, resin reinforced glass ionomer, resin cement with etch-and-rinse adhesive, resin cement with self-etching adhesive, and self-adhesive resin cement. Each group was randomly divided into two equal subgroups, one as a control, and the other to be used experimentally. After 7 days of storage, experimental groups were pressure cycled. The force required to dislodge each post was recorded in Newton (N) on Universal testing machine (Star Testing System) at a crosshead speed of 1 mm/min. Data were statistically analyzed using the ANOVA and Student's t-test (P < 0.001). Results: The pull out strength of posts cemented with zinc phosphate and conventional glass ionomer in pressure cycle group was significantly less than their control group. Although, no significant difference was found between pressure cycle and control group using resin reinforced glass ionomer cement and resin cements. Conclusion: Dentist should consider using resin reinforced glass ionomer or resin cement, for the cementation of glass fiber post, for the patients such as divers, who are likely to be exposed to pressure cycling.